Hawking radiation in Jackiw–Teitelboim gravity - Waheed A. Dar; Prince A. Ganai; Nirmalya Kajuri (European Physical Journal C: Particles and Fields)
Abstract In this paper, we study Hawking radiation in Jackiw–Teitelboim gravity for minimally coupled massless and massive scalar fields. We employ a holography-inspired technique to derive the Bogoliubov coefficients. We consider both black holes in equilibrium and black holes attached to a bath. In the latter case, we compute semiclassical deviations from the thermal spectrum.